DDDR-21. REGULATORY REDUCTASE SUBUNIT RRM2 AND DEHYDROGENASE IMPDH2 INTERACT IN GLIOBLASTOMA IN A TMZ-DEPENDENT MANNER. (14th November 2022) - McManus, Graysen; Perrault, Ella; Shireman, Jack; Ventarapragada, Divya; Lahmadi, Linna; Lin, Peiyu; Ali, Eunis; Park, Cheol; Baisiwala, Shivani; James, David; Ben-Sahra, Issam; Pott, Sebastian; et al.
Abstract: Glioblastoma (GBM) is an aggressive primary brain tumor characterized by poor prognostic outcomes. Nearly all GBM tumors recur, due to cellular resistance against chemotherapies, including temozolomide (TMZ), which develops during active treatment. To investigate these adaptive mechanisms, our lab conducted a single-cell RNA sequencing analysis utilizing an in vivo patient-derived xenograft (PDX) model of GBM, prior to, during, and post TMZ-based therapy. Our data revealed 149 genes to be uniquely expressed in the during-TMZ condition (p < 0.0001), including two regulatory enzymes involved in purine metabolism: the Ribonucleotide Reductase (RNR) Regulatory Subunit 2, RRM2, and inosine monophosphate dehydrogenase 2, IMPDH2. Previous work in this lab has independently established both RRM2 and IMPDH2 as significant drivers of TMZ-resistance in GBM, through their respective abilities to alter tumor metabolism during therapy. Network analysis of genetic pathways enriched during TMZ therapy revealed a previously unidentified interaction between IMPDH2 and the RRM1 subunit of the RNR enzyme. Given these data, we aimed to determine if there was also an interaction between IMPDH2 and RRM2 in GBM. Immunocyto- and histochemistry of GBM-PDX primarily demonstrated significant co-localization between RRM2 and IMPDH2 during TMZ therapy. Immunoprecipitation (IP) and reverse-IP analyses were subsequently conducted, and revealed a previously unreported molecular interaction between the two proteins in GBM lines, which increased in a TMZ-dependent manner. These results were not corroborated in neural stem cell lines. Additionally, immunoblot analyses revealed that in RRM2-knockdown GBM-PDX, IMPDH2 protein expression is decreased compared to controls. We hypothesize the dynamic interaction of RRM2 and IMPDH2 to enhance the metabolic adaptations underlying GBM chemoresistance. The efforts of this study are now focused on investigating the potentially synergistic mechanisms of FDA-approved RRM2 and IMPDH2 inhibitors, previously shown to enhance the efficiency of TMZ. This novel and targetable interaction may present a promising clinical opportunity for GBM therapy.